Caribbean Discourses - Durgasingh, Ryan,Selvon-Ramkissoon, Nicha (Springer International Publishing, 2024)
Chapter 1. Introduction – Part I Tracing the Development of Discourses in the Caribbean – Chapter 2. Styles and Stylistic Change in Creole Languages: Formal Language in the Eastern Maroon Creole – Chapter 3. Towards a Discursive History of the Caribbean as a History of Genres – Part II Discourse and Public Policy in the Caribbean – Chapter 4. Critical Discourse Studies and Curriculum Development in Trinidad and Tobago: Exploring Discursive Practices in Education Policy – Part III Discursive Constructions of the Caribbean Prime Minister – Chapter 5. Taking Responsibility: Conceptual Metaphor and the Accession Stage of Leadership in Eric Williams’ Inward Hunger: The Making of a Prime Minister – Chapter 6. Masking the Critic: A Critical Discourse Analysis of Newspaper Editorials – Chapter 7. “The Most Honourable Brogad”: A Critical Discourse Analysis of Jamaica’s Prime Minister as Hero, Sex Symbol and Villain on Social Media – Part IV Stylistic Appraisals of Caribbean Literary Discourse – Chapter 8. “He Was Oppressed by a Sense of Loss”: Stylistic Constructions of the Tragic in A House for Mr Biswas – Chapter 9. Selvon’s Stylistics: Self-Conscious Language Production in An Island Is a World – Chapter 10. Storifying Caribbean Cricket: Voice and Perspective in Paul Keens-Douglas’s “Tanti at de Oval” – Part V Gender, Media, and Discourse in the Caribbean – Chapter 11. Digital Discourses on Gender-Based Violence in Trinidad and Tobago – Chapter 12. Media Representation of Gender-Based Violence in Two Cases and Related Examples: A Multimodal Discursive Study./. This edited collection represents a first-of-its-kind exploration of English-related discourses in the Caribbean. Drawing from Critical Discourse and stylistic analyses, the book's wide-ranging chapters examine language as it is produced within the complex demographic milieu of the region. It addresses a critical lack of linguistic scholarship on discourse types from the Caribbean, since the major academic focus in the post-independence era has been on descriptive and interventionist work in Creole Linguistics. This volume seeks to add new dimensions to language in practice with its focus on the development of discourse types within the region, public policy, discourses surrounding the galvanising figure of the Caribbean Prime Minister, literary discourses, and gender and media representations. As a site of great variation, linguistic and otherwise, the Caribbean provides unique insight into the interplay of the socio-political and language in contemporary societies in the Global South. Based on work presented at the University of Trinidad and Tobago’s “Stylistics, Critical Discourse Analysis and Language Use in the Caribbean” 2021 conference, the book draws together papers from established Caribbeanists seeking to bridge the existing theoretical and analytical gap between the more macro, socio-political aspects of studies in the social sciences, and the more micro features of linguistic analysis. With its breadth of coverage and analysis, this volume has implications for work being done at all levels of university scholarship in the social sciences, media discourses, decolonisation practices, and language and society in postcolonial and multi-ethnic contexts worldwide. Ryan Durgasingh is a Research Fellow at Ruhr University, Bochum, and PhD candidate at the University of Münster, Germany, where his work focuses on morphosyntactic variation in Caribbean Englishes. His research interests include stylistics, Critical Discourse Studies, variationist sociolinguistics, and corpus-based approaches to linguistic analysis. Nicha Selvon-Ramkissoon is an Assistant Professor at the Centre for Education Programmes, University of Trinidad and Tobago. Her main areas of interest are in Language Arts Curriculum Development, Second Dialect/Language Pedagogy, Critical Discourse Studies, and Translanguaging pedagogy for migrant communities.
10.1007/978-3-031-45047-1
Keywords: Language and languages; Ethnology; Culture.; Latin American literature.; Language policy.; Knowledge; Sociology of.